2015
DOI: 10.1590/0102-33062015abb0078
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seed germination and protocorm development of Cyrtopodium glutiniferum (Orchidaceae) promoted by mycorrhizal fungi Epulorhiza spp.

Abstract: Cyrtopodium glutiniferum is an endemic orchid of Brazil with potential medicinal and ornamental applications. As mycorrhizal fungi are essential for the initiation of the orchid life cycle, the aim of this study was to determine the strains of mycorrhizal fungi suitable for seed germination and protocorm development of C. glutiniferum and to characterize the symbiotic development of protocorms. Seeds of C. glutiniferum were inoculated with nine mycorrhizal fungi, Epulorhiza spp., Ceratorhiza spp., Rhizoctonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
(35 reference statements)
1
22
0
1
Order By: Relevance
“…These authors observed that the average percentage germination and development obtained by using their own isolated species were no different from the averages obtained by using another isolate from Eulophia spectabilis. Additionally, Pereira et al (2015) suggested that Cyrtopodium glutiniferum has a preference for strains of Tulasnella and that fungus digestion is essential to protocorm development. In contrast, these authors observed that the isolates of Ceratorhiza and Rhizoctonia did not promote germination in Cyrtopodium glutiniferum seeds.…”
Section: Germination Testsmentioning
confidence: 99%
“…These authors observed that the average percentage germination and development obtained by using their own isolated species were no different from the averages obtained by using another isolate from Eulophia spectabilis. Additionally, Pereira et al (2015) suggested that Cyrtopodium glutiniferum has a preference for strains of Tulasnella and that fungus digestion is essential to protocorm development. In contrast, these authors observed that the isolates of Ceratorhiza and Rhizoctonia did not promote germination in Cyrtopodium glutiniferum seeds.…”
Section: Germination Testsmentioning
confidence: 99%
“…Germination and formation process of mycorrhizal fungi spore, through 3 stages, i.e, (1) germination of spores in the soil, (2) penetration of hyphae into root cells and (3) development of hyphae in the root cortex (Pereira et al 2015), and these third of stages possibility also be carried out by mycorrhizal fungi in the land contaminated heavy metals in to multiply themselves. The calculation results of the number of mycorrhizal fungi spores in 100 gr of heavy metals contaminated rhizosphere found in different amounts and dominated by the genus Acaulospora sp.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Tolumnia variegata in the presence of Ceratobasidium have a positive influence in seed germination (Otero et al 2005), Epulorhiza spp. promoted protocorm development until leaf production of Cyrtopodium glutiniferum (Pereira et al 2015). Besides, Fusarium spp.…”
Section: Orchid Species Description-pleurothallis Coriacardiamentioning
confidence: 98%